2020
DOI: 10.3390/ijerph17072422
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Polycystic Ovary Syndrome and It’s Comorbidities in Women with Autoimmune Thyroid Disease

Abstract: Objective: To investigate the prevalence of polycystic ovary syndrome (PCOS) and its comorbidities in patients with autoimmune thyroid disease (AITD). Population: In this cohort study, patients newly diagnosed as having Hashimoto thyroiditis (HT) or Grave disease (GD) were recruited into the AITD group. Method: The logistic regression model was used to investigate the association between exposure, endpoint, later diseases and treatment. Main Outcome Measures: We assessed the cumulative incidence using the Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…These results provide significant evidence on the mechanism of DHEA-mediated immune function and effective protection against infectious and inflammatory reactions in animals and humans (27). Moreover, the analysis of the literature shows that the concentration of DHEAS in patients with PCOS positively correlates with better metabolic control and a lower level of inflammatory markers (8). Therefore, it is difficult to explain the reason for the higher concentration of DHEAS in the group of patients with PCOS and AT in our study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…These results provide significant evidence on the mechanism of DHEA-mediated immune function and effective protection against infectious and inflammatory reactions in animals and humans (27). Moreover, the analysis of the literature shows that the concentration of DHEAS in patients with PCOS positively correlates with better metabolic control and a lower level of inflammatory markers (8). Therefore, it is difficult to explain the reason for the higher concentration of DHEAS in the group of patients with PCOS and AT in our study.…”
Section: Discussionmentioning
confidence: 66%
“…There are also other risk factors observed in these women such as oxidative stress, blood clotting disorders, impaired endothelial function, increased arterial stiffness, increased inflammatory markers, or dysfunction of the heart muscle. In patients with PCOS and AT, Ho et al (8) proved an increased risk of diabetes, lipid metabolism disorders, and ischemic heart disease compared with the control group (AT without PCOS). However, an increased risk of strokes in the study group was not stated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest a role of autoimmunity in the pathogenesis of PCOS and women with PCOS have a 5-fold higher risk of HT [ 3 , 18 – 20 ]. Another study reported a three-fold higher prevalence of HT in patients with PCOS [ 3 , 8 , 21 ]. Du and Li aimed to evaluate the relationship between PCOS and thyroid autoimmunity (TAI) by performing a meta-analysis of 6 studies involving 726 PCOS patients and 879 controls and they showed that HT and thyroid autoantibody levels were higher in PCOS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, women with menstrual disorders and sub-fertility are more susceptible to hypothyroidism [ 168 ], and more cases of chronic pelvic pain have been established in endometriosis patients with thyroid dysfunction than in patients without thyroid dysfunction [ 162 ]. In addition, PCOS patients have a higher risk of autoimmune thyroid disease (AITD) compared with normal women [ 169 , 170 , 171 ]. Furthermore, hypothyroidism seems to be associated with poor prognosis in patients with endometrial cancer [ 172 ].…”
Section: Clinical Consequences Of the Crosstalk Between Ths And Repro...mentioning
confidence: 99%